Analysis of Picohydro Power Plant Design on Water Flow and its Utilization - Gv Rian Simare-mare; Bintra Rotua Simbolon (Institute of Computer Science (IOCS), 2024)
Picohydro power plants represent a promising solution for decentralized energy generation in remote and underserved regions, leveraging the natural energy potential of small water flows. This research investigates the design principles, efficiency considerations, and socio-economic impacts of picohydro systems to assess their viability and potential contributions to sustainable development. The study begins with a comprehensive review of existing literature to establish foundational knowledge on picohydro technology and its applications. It then proceeds with empirical analyses, including case studies and field surveys, to gather firsthand data on system performance, water flow dynamics, and community perceptions. Computational simulations further optimize design parameters, such as turbine selection and system configuration, to maximize energy extraction efficiency under varying operational conditions. Key findings highlight the critical role of tailored engineering solutions in enhancing picohydro system performance and reliability. Socio-economic analyses underscore the transformative impact of picohydro installations on improving energy access, supporting local livelihoods, and stimulating economic growth in rural areas. Environmental assessments emphasize the importance of eco-friendly design practices to minimize ecological impacts and ensure sustainable operation.